2021
DOI: 10.3390/biology10111153
|View full text |Cite
|
Sign up to set email alerts
|

Toluene Can Disrupt Rat Ovarian Follicullogenesis and Steroidogenesis and Induce Both Autophagy and Apoptosis

Abstract: Toluene has been shown to be highly toxic to humans and animals and can cause damage to various tissues. However, studies reporting its effects on ovarian function are still limited. In this study, we investigated the in vivo effect of toluene using female Wistar rats. We found that toluene exposure decreased ovarian weight and affected ovarian structure by increasing the number of abnormally growing follicles. Moreover, it significantly increased progesterone and testosterone levels. We also showed that tolue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The immunostaining was investigated as described in our previous studies [ 70 , 71 ]. Slides containing tissue sections were placed on hotplate (60° C) and dewaxed with xylene.…”
Section: Methodsmentioning
confidence: 99%
“…The immunostaining was investigated as described in our previous studies [ 70 , 71 ]. Slides containing tissue sections were placed on hotplate (60° C) and dewaxed with xylene.…”
Section: Methodsmentioning
confidence: 99%
“…Intraperitoneal exposure of rats to toluene at the dose of 900 mg/kg for 6 days caused vacuolar degeneration of hepatocytes and epithelial lining of renal tubules, neuronal damage, and neurodegeneration [16]. Alrezaki, et al [19] found that exposure of non pregnant female rats to toluene inhalation at the doses of 2000, 4000 and 8000 ppm for the duration of 28 days at the rate of 30 min per day increased the peripheral progesterone and testosterone levels, decreased ovarian weight and increased the number of abnormally growing follicles.…”
Section: Discussionmentioning
confidence: 99%